2007
DOI: 10.1063/1.2764444
|View full text |Cite
|
Sign up to set email alerts
|

Third-order intermodulation in two-pole X-band HgBa2CaCu2O6+δ microstrip filters

Abstract: Third-order intermodulation is studied in two-pole X-band high-temperature superconducting (HTS) HgBa2CaCu2O6+δ microstrip filters at >77K. The third-order intercept (IP3) of the HgBa2CaCu2O6+δ filters is consistently higher than that of the YBa2Cu3O7 filter of the same geometry in this temperature range. At 110K, the IP3 of 38dBm remains for the Hg-1212 filters, the best so far achieved at T>100K. The dc critical current density Jc and the rf one JIP3 derived from the IP3 have a similar reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The coincidence of the P c -t curves of the '1212' isomorphic pair suggests that anisotropy of the electronic structure plays a critical role in determining the temperature dependence of the microwave power handing capability. It is worth mentioning that our earlier research on YBCO, Hg-1212 and Tl-2212 has qualitatively demonstrated a correlation between the microwave power handing capability with the anisotropy of the electronic structure [5,6]. Basically, the least anisotropic YBCO has the least susceptibility to t, while the highest anisotropic Tl-2212 experiences the most susceptibility to t. The result shown in figure 2 provides a quantitative demonstration of the correlation between the microwave power handing capability with the anisotropy of the electronic structure of the HTSs.…”
Section: Results and The Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The coincidence of the P c -t curves of the '1212' isomorphic pair suggests that anisotropy of the electronic structure plays a critical role in determining the temperature dependence of the microwave power handing capability. It is worth mentioning that our earlier research on YBCO, Hg-1212 and Tl-2212 has qualitatively demonstrated a correlation between the microwave power handing capability with the anisotropy of the electronic structure [5,6]. Basically, the least anisotropic YBCO has the least susceptibility to t, while the highest anisotropic Tl-2212 experiences the most susceptibility to t. The result shown in figure 2 provides a quantitative demonstration of the correlation between the microwave power handing capability with the anisotropy of the electronic structure of the HTSs.…”
Section: Results and The Discussionmentioning
confidence: 79%
“…Consequently, the '1212' pair shares the same reduced temperature (t = T /T c ) dependence of critical current density J c and irreversibility [3,4]. In a recent study of the microwave nonlinearity in several high temperature superconductors (HTSs) including YBa 2 Cu 3 O 7 (YBCO), Tl 2 Ba 2 CaCu 2 O 8 (Tl-2212) and Hg-1212, the J c and the rf critical current density J IP3 derived from the third-order intercept (IP3) was found to follow a similar t-dependence for each of the three HTSs in the elevated temperature range near T c , suggesting that the magnetic vortex depinning in HTS materials dominates the microwave nonlinearity at elevated temperatures [5,6]. Qualitatively, this observation agrees well with the recent theoretical discussion on the origin of the microwave nonlinearity [7].…”
Section: Introductionmentioning
confidence: 86%
“…From some recent research on microwave nonlinearity of HTS films, the HTS films' microwave power handling or the third intermodulation were related to the films' magnetic vortices pinning strength [20][21][22]. In microwave fields, Tl-2212 films have been widely used, the weak pinning strength will influence the performance of Tl-2212 film made devices, and the enhancement of J c on Tl-2212 films is important and necessary.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of using Tl-2212 as the precursor, the double Tl-O layers in Tl-2212 collapse into one Hg-O layer during the cation exchange, resulting in a shortening of the c axis by 14% from 2.96 nm for Tl-2212 to 1.27 nm for Hg-1212. Using epitaxial Tl-1212 and Tl-2212 films as precursors, epitaxial Hg-1212 thin and thick films have been obtained on dielectric and metal substrates for both electronic [12][13][14][15][16] and electrical devices applications [17,18]. Furthermore, the cation exchange between Hg-1212 films and Tl-1212 (or Tl-2212) films has been found to be fully reversible [10,19].…”
Section: Introductionmentioning
confidence: 99%